2023
DOI: 10.1039/d3qo00501a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed asymmetric (4 + 3) cycloaddition of N-2,2,2-trifluoroethylisatin ketimines: access to optically active spirooxindoles

Abstract: Herein we first report a palladium-catalyzed asymmetric (4+3) cycloaddition of N-2,2,2-trifluoroethylisatin ketimines with 2-methylidenetrimethylene carbonate, affording trifluoromethyl-group-containing spirooxindoles fused with a seven-membered ring as major diastereoisomer in moderate yields with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Based on the experimental observations and previous literature, 6–13 a mechanism was proposed, as shown in Scheme 6. Under the catalysis of the PdL complex, the decarboxylation of sulfonamido-substituted acyclic allylic carbonates 2 results in aza-π-allylpalladium zwitterionic intermediates A along with the extrusion of CO 2 and t BuOH.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the experimental observations and previous literature, 6–13 a mechanism was proposed, as shown in Scheme 6. Under the catalysis of the PdL complex, the decarboxylation of sulfonamido-substituted acyclic allylic carbonates 2 results in aza-π-allylpalladium zwitterionic intermediates A along with the extrusion of CO 2 and t BuOH.…”
Section: Resultsmentioning
confidence: 98%
“…Over the past few years, various precursors have been designed, synthesized and applied for different types of palladium-catalyzed decarboxylative chemical transformations. 6–13 Through in-depth literature research, it was found that the precursors to in situ form π-allylpalladium zwitterionic intermediates via a decarboxylation process mainly include cyclic vinyl carbonates, lactones and oxazolidin-2-ones (Scheme 1a), such as vinylethylene carbonates, 6 2-alkylidenetrimethylene carbonates, 8 γ-methylidene-δ-valerolactones, 9 vinyl benzoxazinones, 10 and vinyl methylene cyclic carbonates. 11 An alternative way for generating π-allylpalladium zwitterionic intermediates is to use acyclic allylic carbonates, and almost all studies focused on Pd-trimethylenemethane (TMM) zwitterionic intermediates containing a ligand-ligated π-allylpalladium cation and a carbanion counterpart (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Li group reported a Pd-catalyzed asymmetric oxa-[4 + 3] dipolar cycloaddition of ADTMCs 1 with N -2,2,2-trifluoroethylisatin ketimines 58 (Scheme 18). 33 Previously, N -2,2,2-trifluoroethylisatin ketimines 58 were utilized as 1,3-dipoles in the presence of a base and underwent [3 + n ] cycloadditions with electron-deficient dipolarophiles or catalytically generated zwitterionic dipoles, typically generating achiral cycloadducts. 34 In this work, an asymmetric oxa-[4 + 3] cycloaddition was achieved using a Pd catalyst and chiral ligand L23 in the absence of a base.…”
Section: Oxa-[4 + 3] Dipolar Cycloadditionsmentioning
confidence: 99%
“…11−25 On the other hand, the generated 1,3dipoles can cycloadd with N,N′-dialkyloxyureas to get a formal (3 + 3) cycloaddition product (Scheme 1b). 26 Alternatively, various vinyl derivatives can be activated under palladium catalysis, and serve as reaction partners to construct asymmetric (3 + 4) cycloaddition 27 and (3 + 5) cycloaddition (Scheme 1b). 28,29 Despite the abovementioned advancement, the construction of infused oxindoles with trifluoromethyl-1,2,4-triazole/triazoline skeleton has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, N -2,2,2-trifluoroethylisatin ketimines were employed as 1,3-dipoles to undergo (3 + 2) or (3 + 4) cycloaddition reactions with alkenes or conjugated dienes, producing spirocyclic oxindoles (Scheme a). On the other hand, the generated 1,3-dipoles can cycloadd with N , N ′-dialkyloxyureas to get a formal (3 + 3) cycloaddition product (Scheme b) . Alternatively, various vinyl derivatives can be activated under palladium catalysis, and serve as reaction partners to construct asymmetric (3 + 4) cycloaddition and (3 + 5) cycloaddition (Scheme b). , Despite the abovementioned advancement, the construction of infused oxindoles with trifluoromethyl-1,2,4-triazole/triazoline skeleton has not been reported. We hypothesized that these new compounds can be achieved by the cycloaddition of N -2,2,2-trifluoroethylisatin ketimines with azodicarboxylates.…”
Section: Introductionmentioning
confidence: 99%